Odpowiedzi

2010-01-31T12:53:12+01:00
A) (a+b)•x +(a+b)•y = (a+b)•(x+y)
b) (5-x)•a+(5-x)•b = (5-x)•(a+b)
c) (2a+b)•y-6•(2a+b) = (2a+b)•(y-6)
d) (4z+3)•x-(4z+3) = (4z+3)•(x-1)
e) x²•(10a-1) -x•(10a-1) = (10a-1)•(x²-x) = (10a-1)•(x-1)•x
f) (7b-5a)•(x+y)+(x-y)•(7b-5a) = (7b-5a)•[(x+y)+(x-y)] = (7b-5a)•2x
2 4 2
2010-01-31T14:34:35+01:00
A) (a+b)x +(a+b)y = (a+b)(x+y)
b) (5-x)a+(5-x)b = (5-x)(a+b)
c) (2a+b)y-6(2a+b) = (2a+b)(y-6)
d) (4z+3)x-(4z+3) = (4z+3)(x-1)
e) x²(10a-1) -x(10a-1) = (10a-1)-(x²-x) = (10a-1)-x(x-1)
f) (7b-5a)(x+y)+(x-y)(7b-5a) = (7b-5a)((x+y)+(x-y)) = (7b-5a)2x
2 3 2